Adsorption Characteristics of a Zn-Porphyrin on MgO Surfaces - Killian, Manuela; Wagener, Victoria; Schmuki, Patrik (Surface and Interface Analysis, 2013)
Time-of-flight SIMS was used to study monolayers of the siloxane terminated porphyrin Zn-TESP (C67H75N5O5SiZn) attached to magnesium oxide (MgO) substrates in a silanisation reaction. Time-of-flight SIMS spectra show dependence of the coverage on the preparation temperature. The fragmentation pattern of the porphyrin suggests a strong bond formation to MgO, as was previously reported for SiO2. No signal of physisorbed porphyrin—as previously described for TiO2—could be detected, indicating chemisorbed species under all investigated preparation condition
Keywords: ToF-SIMS; porphyrin; SAM; magnesium oxide; adsorption

A generic interface to reduce the efficiency-stability-cost gap of perovskite solar cells - Hou, Yi; Du, Xiaoyan; Scheiner, Simon; McMeekin, David P.; Wang, Zhiping; Li, Ning; Killian, Manuela; Chen, Haiwei; Richter, Moses; Levchuk, Ievgen; Schrenker, Nadine; Spiecker, Erdmann; et al. (Science, 2017)
A major bottleneck delaying the further commercialization of thin-film solar cells based on hybrid organohalide lead perovskites is the interface losses in state-of-the-art devices. We present a generic interface architecture that combines solution-processed, reliable, and cost-efficient hole-transporting materials, without compromising efficiency, stability or scalability of perovskite solar cells. Tantalum doped tungsten oxide (Ta-WOx)/conjugated polymer multilayers offer a surprisingly small interface barrier and form quasi-ohmic contacts universally with various scalable conjugated polymers. Using a simple regular planar architecture device, Ta-WOx doped interface-based perovskite solar cells achieve maximum efficiencies of 21.2% and combined with over 1000 hours of light stability based on a self-assembled monolayer. By eliminating additional ionic dopants, these findings open up the whole class of organics as scalable hole-transporting materials for perovskite solar cell

A High-Field Anodic NiO Nanosponge with Tunable Thickness for Application in p-Type Dye-Sensitized Solar Cells - Sultan, Umair; Ahmadloo, Farzaneh; Cha, Gi; Gökcan, Baris; Hejazi, Seyedsina; Yoo, Jeong Eun; Nguyen, Nhat Truong; Altomare, Marco; Schmuki, Patrik; Killian, Manuela (ACS Applied Energy Materials, 2020)
Dye-sensitized photocathodes have the potential to significantly contribute to the efficiency of the solar light-to-current conversion in tandem dye-sensitized solar cells (DSSCs). A novel, highly porous nanoarchitecture of NiO is developed in this project. The spongelike material is grown by anodization, shows a virtually crack-free morphology, strongly adheres to the substrate, and can be grown with a controllable thickness of at least up to 6.5 mu m. The oxide composition is NiO and the nanosponge exhibits p-type semiconductive behavior. A doubling of the maximum reported p-type DSSC efficiency compared to coumarin C343-sensitized NiO nanoparticle photocathodes can be achieved with the NiO nanosponge. The developed dye-sensitized p-type NiO-based cathodes are promising for application as photocathodes in tandem DSSC devices.
CRIS-Team WoS Importer:2020-09-18

Albumin Coating on Magnesium via Linker Molecules – Comparing Different Coating Mechanisms - Wagener, Victoria; Killian, Manuela; Turhan, Can Metehan; Virtanen, Sannakaisa (Colloids and Surfaces B-Biointerfaces, 2013)
As magnesium is a non-toxic and biodegradable metal, it is gaining more and more interest in the biomedical sector. The biodegradability is due to the corrosion of Mg in aqueous, chloride containing environment, as it is present in the body. However, corrosion of pure magnesium occurs too fast and takes place inhomogeneously on the metal surface. Moreover, Mg dissolution is connected with strong hydrogen evolution. Therefore alloying and/or coating of magnesium seem to be promising approaches to slow down corrosion and in return hydrogen evolution. This study explores coating of Mg with albumin via three different linker molecules, aminopropyl-triethoxysilane (APTES) plus ascorbic acid (VitC), carbonyldiimidazole (CDI) and stearic acid (SA). The metal samples were first passivated and after the pre-coating with the linker molecules the protein coating took place by soaking the pre-treated samples in an aqueous albumin solution. The immersion time was varied from 0.25 h up to 24 h. The success and the quality of the different coatings were documented by X-ray Photoelectron Spectroscopy (XPS) and Time of Flight Secondary Ion Mass Spectrometry (ToF-SIMS). Pre-coatings were additionally characterized by contact angle and surface roughness measurements. Electrochemical measurements were carried out in simulated body fluid (SBF) to characterize the coatings in view of their corrosion behavior. Albumin coatings could be produced with every linker molecule investigated. Certain protective effects were observed already for linker SAM coated Mg, overall the systems CDI-BSA and SA-BSA showed the best corrosion resistances.
Keywords: Protein coating; bio-degradation; magnesium; electrochemical impedance spectroscopy; albumin

Anodic Nanotubular/porous Hematite Photoanode for Solar Water Splitting: Substantial Effect of Iron Substrate Purity - Lee, Chong-Yong; Wang, Lei; Kado, Yuya; Killian, Manuela; Schmuki, Patrik (ChemSusChem, 2014)
Anodization of iron substrates is one of the most simple and effective ways to fabricate nanotubular (and porous) structures that could be directly used as a photoanode for solar water splitting. Up to now, all studies in this field focused on achieving a better geometry of the hematite nanostructures for a higher efficiency. The present study, however, highlights that the purity of the iron substrate used for any anodic-hematite-formation approach is extremely important in view of the water-splitting performance. Herein, anodic self-organized oxide morphologies (nanotubular and nanoporous) are grown on different iron substrates under a range of anodization conditions, including elevated temperatures and anodization supported by ultrasonication. Substrate purity has not only a significant effect on oxide-layer growth rate and tube morphology, but also gives rise to a ninefold increase in the photoelectrochemical water-splitting performance (0.250 vs. 0.028mA cm-2 at 1.40V vs. reversible hydrogen electrode under AM1.5 100mW cm-2 illumination) for 99.99 % versus 99.5 % purity iron substrates of similar oxide geometry. Elemental analysis and model alloys show that particularly manganese impurities have a strong detrimental effect on the water-splitting performance.
EAM Import::2019-03-13

Controlling the diameter of aligned single-walled carbon nanotubes on quartz via catalyst reduction time - Schweiger, Manuel; Schaudig, Maximilian; Gannott, Florentina; Killian, Manuela; Bitzek, Erik; Schmuki, Patrik; Zaumseil, Jana (Carbon, 2015)
One of the main objectives of chemical vapor deposition (CVD) growth of single-walled carbon nanotubes (SWCNT) is control over their diameter and type (metallic or semiconducting). Here, we investigate the evolution of iron catalyst particles on quartz substrates depending on the duration of the reduction step with hydrogen and its effect on the growth of horizontally aligned SWCNT. We find a strong dependence of catalyst particle size and size distribution on the initial iron film thickness and the reduction time at 630 °C. Initial decrease of the particle size is followed by an unexpected increase. Statistical analysis of the Raman radial breathing modes of the SWCNT over large areas gave reliable and reproducible diameter distributions that correlated directly with the catalyst particle size distributions. By changing the reduction time it was possible to reproducibly shift the average SWCNT diameter from 1.5 (±0.3) nm to 1.2 (±0.2) nm while maintaining a nanotube density of 5–6 SWCNT/ extgreekmm. In order to describe the evolution of the particle size during the reduction process at this particular temperature, we propose a model that includes the diffusion of iron into the quartz and its re-emergence.
WW1::1053
Keywords: Simulation and Modeling

Electrochemical polymerization and characterization of polypyrrole on Mg-Al alloy (AZ91D) - Turhan, Can Metehan; Weiser, Martin; Killian, Manuela; Leitner, Bernhard; Virtanen, Sannakaisa (Synthetic Metals, 2011)

Electronically Tuned Asymmetric meso-Substituted Porphyrins for p-Type Solar Cells - Grzegorzek, Norbert; Zieleniewska, Anna; Schür, Annika; Maichle-Mössmer, Cäcilia; Killian, Manuela; Guldi, Dirk Michael; Chernick, Erin T. (ChemPlusChem, 2019)
A series of electronically tuned asymmetric porphyrins have been synthesized for use in p-type solar cells. The porphyrin derivatives were strategically designed with electron-withdrawing capability and an electronic dipole gradient to aid in electron-harvesting capacity from a nickel oxide cathode. Specifically, the porphyrins were substituted at the meso position with different arrangements of the electron-withdrawing pentafluorobenzene moiety, electron-donating/coordinating 4-pyridyl ligand, and an electron withdrawing/synthetically modifiable 4-cyanophenyl unit. Two distinct free-base porphyrins were synthesized, one of which was further metallated with nickel(II). The porphyrins were fully characterized and their electronic properties explored experimentally by electrochemistry, and both steady state and time-resolved spectroscopy. Finally, the porphyrins were incorporated into a p-type solar cell device utilizing NiO as the cathode, and demonstrating a preliminary maximum performance of η(%)=0.082 and IPCE MAX (%)=26.0 without co-sensitization.
CRIS-Team Scopus Importer:2019-05-28
Keywords: dye-sensitized solar cells; light harvesting; nickel; photosensitizers; porphyrinoids

Embedded Palladium Activation as a Facile Method for TiO2 - Mazare, Anca Valentina; Liu, Ning; Lee, Kiyoung; Killian, Manuela; Schmuki, Patrik (ChemistryOpen, 2013)
A direct and efficient way to decorate TiO2 nanotubes with copper, Cu2O and CuO particles is shown. Active palladium species embedded in the TiO2 nanotube walls allow specific initiation sites to be triggered for electroless copper deposition. These Cu2O-decorated TiO2 nanotubes could be used for water splitting.
EAM Import::2019-03-14

Fibronectin Functionalized Electrospun Fibers by Using Benign Solvents: Best Way to Achieve Effective Functionalization - Liverani, Liliana; Killian, Manuela; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2019)
The aim of this study is to demonstrate the feasibility of different functionalization methods for electrospun fibers developed using benign solvents. In particular three different approaches were investigated to achieve the functionalization of poly(epsilon caprolactone) (PCL) electrospun fibers with fibronectin. Protein surface entrapment, chemical functionalization and coaxial electrospinning were performed and compared. Moreover, bilayered scaffolds, with a top patterned and functionalized layer with fibronectin and a randomly oriented not functionalized layer were fabricated, demonstrating the versatility of the use of benign solvents for electrospinning also for the fabrication of complex graded structures. Besides the characterization of the morphology of the obtained scaffolds, ATR-FTIR and ToF-SIMS were used for the surface characterization of the functionalized fibers. Cell adhesion and proliferation were also investigated by using ST-2 cells. Positive results were obtained from all functionalized scaffolds and the most promising results were obtained with bilayered scaffolds, in terms of cells infiltration inside the fibrous structure.
CRIS-Team WoS Importer:2019-04-16

Functionalization of Metallic Magnesium with Protein Layers via Linker Molecules - Killian, Manuela; Wagener, Victoria; Schmuki, Patrik; Virtanen, Sannakaisa (Langmuir, 2010)
We present an innovative method to cover pure magnesium with protein monolayers by utilizing the OH termination of the oxide surface and silane coupling chemistry. The protein of interest was albumin. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) were used to monitor the success of the treatment. The attachment of proteins via linker groups yielded smoother and more homogeneous surfaces than coatings produced by steeping magnesium in protein solution. A positive effect on the corrosion behavior of pure magnesium was also observed.

Incorporation of bioactive glass nanoparticles in electrospun PCL/chitosan fibers by using benign solvents - Liverani, Liliana; Lacina, Jonas; Roether, Judith; Boccardi, Elena; Killian, Manuela; Schmuki, Patrik; Schubert, Dirk W.; Boccaccini, Aldo R. (Bioactive Materials, 2018)

Interface Chemistry and Molecular Bonding of Functional Ethoxysilane-Based Self-Assembled Monolayers on Magnesium Surfaces - Killian, Manuela; Seiler, Steffen; Wagener, Victoria; Hahn, Robert; Ebensperger, Christina; Meyer, Bernd; Schmuki, Patrik (ACS Applied Materials and Interfaces, 2015)
The modification of magnesium implants with functional organic molecules is important for increasing the biological acceptance and for reducing the corrosion rate of the implant. In this work, we evaluated by a combined experimental and theoretical approach the adsorption strength and geometry of a functional self-assembled monolayer (SAM) of hydrolyzed (3-aminopropyl)triethoxysilane (APTES) molecules on a model magnesium implant surface. In time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS), only a minor amount of reverse attachment was observed. Substrate–O–Si signals could be detected, as well as other characteristic APTES fragments. The stability of the SAM upon heating in UHV was investigated additionally. Density-functional theory (DFT) calculations were used to explore the preferred binding mode and the most favorable binding configuration of the hydrolyzed APTES molecules on the hydroxylated magnesium substrate. Attachment of the molecules via hydrogen bonding or covalent bond formation via single or multiple condensation reactions were considered. The impact of the experimental conditions and the water concentration in the solvent on the thermodynamic stability of possible APTES binding modes is analyzed as a function of the water chemical potential of the environment. Finally, the influence of van der Waals contributions to the adsorption energy will be discussed.
Keywords: DFT calculations; magnesium; self-assembled monolayer; silane coupling; ToF-SIMS

Key factors for an improved lithium ion storage capacity of anodic TiO2 nanotubes - Kirchgeorg, Robin; Kallert, Max; Liu, Ning; Hahn, Robert; Killian, Manuela; Schmuki, Patrik (Electrochimica Acta, 2016)
In the present work we investigate key factors that influence the Li-storage capacity of anodically grown self-organized TiO2 nanotube layers. First, the influence of both tube length and top morphology are investigated regarding the rate performance of the nanotube layers. Then, factors such as the presence of initiation (grass) layers and the influence of the double walled morphology of conventional TiO2 nanotube layers are elaborated. At high C-rates a grass layer even shows a beneficial contribution, mainly by adding to the double layer capacitance. The presence of a double wall morphology and the associated carbon contamination lead to a lower intercalation ability. Two different approaches are taken to eliminate the inner carbon-rich layer: Cathodic polarization and tube formation in DMSO based electrolytes. This results in an enhancement of the areal capacity by 17% and 33% compared to unmodified tube layers for the two approaches.
EAM Import::2019-03-12

Novel Fully Organic Water Oxidation Electrocatalysts: A Quest for Simplicity - Wu, Yanlin; Klein, Volker; Killian, Manuela; Behling, Christopher; Chea, Sany; Tsogoeva, Svetlana; Bachmann, Julien (ACS Omega, 2018)
Despite the growing need for readily available and inexpensive catalysts for the half-reactions involved in water splitting, water oxidation and reduction electrocatalysts are still traditionally based on noble metals. One long-standing challenge has been the development of an oxygen evolution reaction catalyzed by easily available, structurally simple, and purely organic compounds. Herein, we first generalize the performance of the known N-ethyl-flavinium ion to a number of derivatives. Furthermore, we demonstrate an unprecedented application of different pyridinium and related salts as very simple, inexpensive water oxidation organocatalysts consisting of earth-abundant elements (C, H, O, and N) exclusively. The results establish the prospects of heterocyclic aromatics for further design of new organic electrocatalysts for this challenging oxidation reaction.

Overcoming Interfacial Losses in Solution-Processed Organic Multi-Junction Solar Cells - Du, Xiaoyan; Lytken, Ole; Killian, Manuela; Cao, Jiamin; Stubhan, Tobias; Turbiez, Mathieu; Schmuki, Patrik; Steinrück, Hans-Peter; Ding, Liming; Fink, Rainer; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2016)
Organic solar cells are promising in terms of full-solution-processing which enables low-cost and large-scale fabrication. While single-junction solar cells have seen a boost in power conversion efficiency (PCE), multi-junction solar cells are promising to further enhance the PCE. In all-solution-processed multi-junction solar cells, interfacial losses are often encountered between hole-transporting layer (HTL) and the active layers and therefore greatly limit the application of newly developed high-performance donor and acceptor materials in multi-junction solar cells. Here, the authors report on a systematic study of interface losses in both single-junction and multi-junction solar cells based on representative polymer donors and HTLs using electron spectroscopy and time-of-flight secondary ion mass spectrometry. It is found that a facile mixed HTL containing poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) and MoO nanoparticles successfully overcomes the interfacial losses in both single- and multi-junction solar cells based on various active layers by reducing interface protonation, promoting better energy-level alignment, and forming a dense and smooth layer. Solution-processed single-junction solar cells are demonstrated to reach the same performance as with evaporated MoO (over 7%). Multi-junction solar cells with polymers containing nitrogen atoms as the first layer and the mixed PEDOT:PSS and MoO nanoparticles as hole extraction layer reach fill factor (FF) of over 60%, and PCE of over 8%, while the identical stack with pristine PEDOT:PSS or MoO nanoparticles show FF smaller than 50% and PCE less than 5%.
Keywords: Interfacial losses; Organic multi-junction solar cells; Organic photovoltaics; Recombination layer; Solution-processing

Photocatalytic properties of in situ doped TiO2-nanotubes grown by rapid breakdown anodization - Hahn, Robert; Stark, Martin; Killian, Manuela; Schmuki, Patrik (Catalysis: Science and Technology, 2013)
In the present work, we demonstrate an in situ electrochemical doping approach during the growth of TiO2 nanotubular layers formed by rapid breakdown anodization (RBA). For this, several oxygen containing metal anions, as doping species (WO42-, Al(OH)4-, SiO32-, MoO42-, SnO44-, CrO42- and MnO4-), were investigated as additives to the electrolyte and successfully incorporated into the nanotubular oxide during the ultrafast tube growth. A linear relationship between the concentration of anions in the electrolyte and the doping concentration in the oxide was found. The resulting doped layers were tested, after heat treatment, for their UV photocatalytic activity using the degradation of AO7 (an organic model compound routinely used for determining the kinetics of photocatalytic decomposition reactions).
EAM Import::2019-03-12

Physical vapor deposition of [EMIM][Tf2N]: A new approach to the modification of surface properties with ultrathin ionic liquid films - Cremer, Till; Killian, Manuela; Gottfried, Michael; Paape, Natalia; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2008)
Ultrathin films of the ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [EMIM][TfN], are prepared on a glass substrate by means of an in situ thermal-evaporation/condensation process under ultrahigh-vacuum conditions. By using X-ray photoelectron spectroscopy (XPS), it is demonstrated that the first layer of the IL film grows two dimensionally, followed by the three-dimensional growth of successive layers. The first molecular layer consists of a bilayer, with the [EMIM] cations in contact to the surface and the [TfN] anions at the vacuum side. The ultrathin IL films are found to be stable under ambient conditions. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Porphyrins as Multifunctional Interconnects in Networks of ZnO Nanoparticles and their Application in Dye-Sensitized Solar Cells - Düring, Jasmin; Kunzmann, Andreas; Killian, Manuela; Costa, Ruben Dario; Guldi, Dirk Michael; Gröhn, Franziska (Chemphotochem, 2018)
ZnO nanoparticles of 2.6 to 4.0 nm in size were interconnected by meso-tetra(4-carboxyphenyl)porphyrin (TCPP) for the realization of novel ZnO–TCPP networks, reaching lateral dimensions ranging from 50 to 800 nm. The resulting ZnO–TCPP networks were probed by dynamic light-scattering experiments, transmission electron microscopy, and spectroscopy, and were also tested as photoactive top layers in TiO2 and ZnO dye-sensitized solar cells (DSSCs). Control over these ZnO–TCPP networks on top of the semiconductor electrodes enables efficiency increases of 10 % and 46 % for TiO2- and ZnO-based photoelectrodes, respectively. In other words, effects, such as reducing the electron recombination and increasing the electron lifetime, document the benefits of using tailored functional hybrid systems in DSSCs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: dye-sensitized solar cells; electron transfer; hybrid assemblies; porphyrins; semiconductor nanoparticles

Protein interactions with corroding metal surfaces: Comparison of Mg and Fe - Wagener, Victoria; Faltz, Anne-Sophie; Killian, Manuela; Schmuki, Patrik; Virtanen, Sannakaisa (Faraday Discussions, 2015)
The influence of bovine serum albumin (BSA) on the electrochemical behaviour of pure Mg and Fe was studied in simulated body fluid (SBF), in view of the possible application of these materials as biodegradable metals. Results indicate a different trend for the BSA-effect on corrosion for the two metals: for Mg, a strong corrosion-inhibiting effect is observed in the presence of BSA in solution, especially for short-term exposure, whereas for Fe only a slight acceleration of corrosion is caused by the addition of BSA to the solution. For both metals, the protein-effect on the electrochemical behaviour shows a complex time-dependence. Surface analysis indicates that stronger BSA adsorption takes place on Mg than on Fe. Moreover, adsorption experiments with BSA and a second protein (lysozyme) were conducted. The results are discussed in view of electrostatic interactions between differently charged metal oxide/hydroxide surfaces and proteins.

Protein interactions with layers of TiO2 nanotube and nanopore arrays: Morphology and surface charge influence - Kulkarni, Mukta; Mazare, Anca Valentina; Park, Jung Hyun; Gongadze, Ekaterina; Killian, Manuela; Kralj, Slavko; Mark, Klaus; Iglic, Ales; Schmuki, Patrik (Acta Biomaterialia, 2016)
In the present work we investigate the key factors involved in the interaction of small-sized charged proteins with TiO2 nanostructures, i.e. albumin (negatively charged), histone (positively charged). We examine anodic nanotubes with specific morphology (simultaneous control over diameter and length, e.g. diameter - 15, 50 or 100nm, length - 250nm up to 10?m) and nanopores. The nanostructures surface area has a direct influence on the amount of bound protein, nonetheless the protein physical properties as electric charge and size (in relation to nanotopography and biomaterial's electric charge) are crucial too. The highest quantity of adsorbed protein is registered for histone, for 100nm diameter nanotubes (10?m length) while higher values are registered for 15nm diameter nanotubes when normalizing protein adsorption to nanostructures' surface unit area (evaluated from dye desorption measurements) - consistent with theoretical considerations. The proteins presence on the nanostructures is evaluated by XPS and ToF-SIMS; additionally, we qualitatively assess their presence along the nanostructures length by ToF-SIMS depth profiles, with decreasing concentration towards the bottom.Surface nanostructuring of titanium biomedical devices with TiO2 nanotubes was shown to significantly influence the adhesion, proliferation and differentiation of mesenchymal stem cells (and other cells too). A high level of control over the nanoscale topography and over the surface area of such 1D nanostructures enables a direct influence on protein adhesion. Herein, we investigate and show how the nanostructure morphology (nanotube diameter and length) influences the interactions with small-sized charged proteins, using as model proteins bovine serum albumin (negatively charged) and histone (positively charged). We show that the protein charge strongly influences their adhesion to the TiO2 nanostructures. Protein adhesion is quantified by ELISA measurements and determination of the nanostructures' total surface area. We use a quantitative surface charge model to describe charge interactions and obtain an increased magnitude of the surface charge density at the top edges of the nanotubes. In addition, we track the proteins presence on and inside the nanostructures. We believe that these aspects are crucial for applications where the incorporation of active molecules such as proteins, drugs, growth factors, etc., into nanotubes is desired.
EVALuna2:10222

Reactivity of TiO2 Nanotube-Supported Platinum Particles in the CO Oxidation Reaction - Krick Calderon, Sandra; Grabau, Mathias; Yoo, Jeong Eun; Killian, Manuela; Schmuki, Patrik; Steinrück, Hans-Peter; Papp, Christian (ChemCatChem, 2017)
The CO oxidation on different platinum model catalysts, in particular differently sized Pt particles on vertically aligned TiO nanotubes (d=80, l=200nm) was investigated by near-ambient-pressure X-ray photoelectron spectroscopy and simultaneous online gas analysis. The results are compared to the behavior on a TiO(110) rutile crystal with a similar Pt coverage and a Pt(111) single crystal. Temperature-programmed reaction experiments at total pressures of 10 to 1.0mbar, and a CO/O ratio of 1:4 were performed to evaluate the reactivity of the samples. The onset temperature of the reaction on the Pt/TiO nanotube samples was found to be lower than on Pt(111) and Pt/TiO(110) and to decrease with decreasing particle size. For all particle samples, a steep increase in reaction rate at a defined temperature was observed, and at high temperatures the reaction became mass transfer-limited in all cases. Isothermal measurements showed that no CO is adsorbed on the particles when CO oxidation has a high activity and metallic platinum is the active catalyst. Ageing of the TiO-supported samples is observed resulting in changes of the reaction onset and CO conversion.
Keywords: Nanotubes; Oxidation; Platinum; Supported catalysts; X-ray absorption spectroscopy

Suppressing the Surface Recombination and Tuning the Open-Circuit Voltage of Polymer/Fullerene Solar Cells by Implementing an Aggregative Ternary Compound - Galli, Diana; Gasparini, Nicola; Forster, Michael; Eckert, Anika; Widling, Christian; Killian, Manuela; Avgeropoulos, Apostolos; Gregoriou, Vasilis G.; Scherf, Ullrich; Chochos, Christos L.; Brabec, Christoph; Ameri, Tayebeh (ACS Applied Materials and Interfaces, 2018)
In this work, we present a novel small molecule based on dithienylthienothiadiazole units (named SM1) acting as an efficient component in ternary blend organic solar cells to modify the hole extraction at the interface. Our findings show that the SM1 suppresses the surface recombination and enhances the open-circuit voltage (Voc). By introducing SM1 in a host system composed of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), we obtained Voc values of up to 0.75 V and fill factors larger than 70% for the ternary blends. As a consequence, the power conversion efficiency is improved by about 30% compared to P3HT:PCBM binary devices. Interestingly, external quantum efficiency and absorption spectra in the near-infrared region do not show any contribution of SM1 in dried films. Instead, the addition of the small molecule improves the Voc by reducing the surface recombination losses. To shed light on the recombination processes, we carried out Fourier-transform photocurrent spectroscopy and impedance spectroscopy measurements. This work shows that the ternary concept can also have functionalities other than photosensitization and can even act as a morphology-directing agent or an interface modifie
Keywords: open-circuit voltages; recombination losses; ternary organic solar cells; sensitizers; small molecules

Ta-Doped TiO2 Nanotubes for Enhanced Solar-Light Photoelectrochemical Water Splitting - Altomare, Marco; Lee, Kiyoung; Killian, Manuela; Selli, Elena; Schmuki, Patrik (Chemistry - A European Journal, 2013)
A little dopey: Ta-doped titania (TiO2) nanotube (NT) arrays can be grown by electrochemical anodization onto low-Ta-concentration (0.03–0.4at % Ta) Ti–Ta alloys. Under optimized conditions (0.1at % Ta, annealing at 650 °C and 7 extgreekmm thickness), Ta-doped TiO2 NT arrays show a significantly enhanced activity in photoelectrochemical water splitting under simulated sunlight conditions.
EAM Import::2019-03-12

TEM and ToF-SIMS studies on the corrosion behavior of vanadium and chromium containing WC-Co hard metals in alkaline solutions - Kellner, Florian; Killian, Manuela; Yang, Guang; Spiecker, Erdmann; Virtanen, Sannakaisa (International Journal of Refractory Metals and Hard Materials, 2011)
The corrosion behavior of hard metals with VC and Cr_3C_2 grain growth inhibitors was investigated in alkaline solutions by electrochemical methods. The two inhibitors have opposite effects on the corrosion behavior: Cr_3C_2 significantly improves the corrosion behavior, whereas VC-containing alloys show a poor resistance. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and analytical transmission electron microscopy (TEM) analyses of the distributions of Cr and V in the composite material, as well as in the surface layers formed during corrosion were employed to clarify the influence of these elements on the corrosion behavior. The measurements showed that VC is precipitated mostly along the WC/binder interface after the liquid-phase sintering process, while Cr_3C_2 is almost homogeneously dissolved in the binder. As VC is chemically instable in alkaline solutions, it completely dissolves out of the binder. In accordance with this observation no V was found in the corrosion product layer on the surface. As WC is more noble than Co, galvanic coupling between the two phases reinforces the Co dissolution, while the WC-phase is protected cathodically. Contrary to VC, chromium is stable in alkaline environments and forms a passivating Cr_2O_3 layer. Enrichment of Cr in the corrosion product layers was detected by TEM and ToF-SIMS. Due to surface passivation by Cr_2O_3, galvanic coupling effects between Co and WC play a much less important role in the corrosion process of the composite material.

ToF-SIMS and XPS studies of the adsorption characteristics of a Zn-porphyrin on TiO2 - Killian, Manuela; Gnichwitz, Jan-Frederik; Hirsch, Andreas; Schmuki, Patrik; Kunze, Julia (Langmuir, 2010)
Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) were used to study monolayers (ML) and thick films of porphyrin Zn-TESP (CHNO SiZn) attached to titanium dioxide (TiO) substrates via silanization. Films on ideal hydroxyl-terminated silicon (SiO) surfaces were used for comparison. ToF-SIMS and XPS spectra show that the type of adsorption varies depending on the thickness of the organic film, the preparation temperature, and the adsorption time. We show that the intensity of a molecular peak at mass 1121.5 u in ToF-SIMS can be used as a direct measure of the ratio of chemisorption/physisorption of Zn-TESP. On TiO, the amount of chemisorbed porphyrin can be increased by increasing the reaction temperature and time during the silanization process. On the SiO reference, only chemisorbed species were detected under all investigated preparation conditions. The present work thus not only gives information on the Zn-TESP linkage to TiO but provides a direct tool for generally determining the type of adsorption of monolayers. © 2009 American Chemical Society.

Topographical study of TiO2 nanostructure surface for photocatalytic hydrogen production - Cha, Gi; Lee, Kiyoung; Yoo, Jeong Eun; Killian, Manuela; Schmuki, Patrik (Electrochimica Acta, 2015)
In the present work we investigate the photocatalytic hydrogen production (water splitting) activity of different Pt loaded TiO2 nanotube layers. Therefore, we fabricate free standing membranes and fix them in four different configurations: top up (with initiation layer ``grass'' or without) and bottom up (bottom closed or open), then decorate the tubes with various amounts of Pt and measure the open-circuit photocatalytic H2 production rate. We find a strong influence of the configuration with the open top morphology showing the highest photocatalytic hydrogen production efficiency, these nanotubes yield 3.5 times more H2 than the least efficient structure (bottom closed). The work therefore provides valuable guidelines for optimizing TiO2 nanotube layers for photocatalytic applications.
EAM Import::2019-03-13

Zirconia nanotube coatings - UV-resistant superhydrophobic surfaces - Raghu, Swathi Naidu Vakamulla; Chuluunbandi, Khajidkhand; Killian, Manuela (Surfaces and Interfaces, 2021)
Surface modifications influence material interactions such as wettability, imparting hydrophobicity or hydrophilicity. Mainstream research focused on enhancing product shelf-life directs attention towards superhydrophobic surfaces (SHS). SHS offer several benefits for out-door applications such as self-cleaning, antisoiling, anti-mist etc. Recently, such surfaces were created by hydrophobization of anodized titania, which although effective lacked a long-term stability of their hydrophobic modifications due to it being susceptible to UV-mitigated degradation. In light of this situation, ZrO2-nanotubes are evaluated with regard to their application as transparent UV-stable superhydrophobic coatings. Nanostructured oxide surfaces are created via singlestep electrochemical anodization. The absence of HF acid-based pre-etching steps offer a safe and alternatively a green synthesis route. Anodized oxides are modified using octadecylphosphonic acid (OPA) self-assembled monolayers, demonstrate superhydrophobicity and are at par with conventionally employed coatings such as PTFE, PFDPA and PTES. The OPA-coatings are evaluated for their mechanical stability under a jet of water, chemical stability under indirect sunlight irradiation in air/water and direct UV exposure. Zirconia nanotubular films were evaluated for optical transparency using light microscopy and surface wettability of the different zirconia-composites was compared to the model system - titania. Structural and compositional differences of the SAM layer upon time dependent decay were analyzed with X-ray photoelectron spectroscopy.
CRIS-Team WoS Importer:2021-10-08